2015
DOI: 10.1165/rcmb.2014-0158oc
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleotide-Binding Domain, Leucine-Rich Repeat Protein 3 Inflammasome/IL-1 Receptor I Axis Mediates Innate, but Not Adaptive, Immune Responses after Exposure to Particulate Matter under 10 μm

Abstract: Exposure to particulate matter (PM), a major component of air pollution, contributes to increased morbidity and mortality worldwide. Inhaled PM induces innate immune responses by airway epithelial cells that may lead to the exacerbation or de novo development of airway disease. We have previously shown that 10-μm PM (PM10) activates the nucleotide-binding domain, leucine-rich repeat protein (NLRP) 3 inflammasome in human airway epithelial cells. Our objective was to determine the innate and adaptive immune res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 60 publications
3
75
0
Order By: Relevance
“…A recent paper demonstrated that particulate matter, known to facilitate allergic sensitization, could also induce uric acid production by airway ECs, but in a TLR4‐independent manner . Although particulate matter was able to activate an innate response in ECs via NLRP3/IL‐1β inflammasome pathway, this pathway was completely dispensable for the facilitation of allergic sensitization . In agreement with these findings, we found that the type 2 immunity‐promoting effect of uric acid was not dependent on NLRP3/IL‐1β signaling, nor was it affected by the lack of ASC or caspase‐1 .…”
Section: Barrier Epithelial Cells In the Lung Play An Important Role supporting
confidence: 88%
“…A recent paper demonstrated that particulate matter, known to facilitate allergic sensitization, could also induce uric acid production by airway ECs, but in a TLR4‐independent manner . Although particulate matter was able to activate an innate response in ECs via NLRP3/IL‐1β inflammasome pathway, this pathway was completely dispensable for the facilitation of allergic sensitization . In agreement with these findings, we found that the type 2 immunity‐promoting effect of uric acid was not dependent on NLRP3/IL‐1β signaling, nor was it affected by the lack of ASC or caspase‐1 .…”
Section: Barrier Epithelial Cells In the Lung Play An Important Role supporting
confidence: 88%
“…DE-associated augmentation of select allergenic phenomena was shown in a human nasal model,15 16 and similar findings were noted with other particulate exposures 17 18. Still, DE's enhancement of allergenic effects has never been demonstrated in vivo in the distal human lung, a site of pathological importance in allergic disease, and the underlying details of this potential synergy are poorly understood.…”
Section: Introductionmentioning
confidence: 60%
“…The expression of NOD1 has been shown to be downregulated during pollen season among patients with allergic rhinitis [20], and its normal activation can reduce airway hyperresponsiveness accompanied by a reduction of allergen-specific T-cell proliferation in allergen-induced lung inflammation [21]. NLRP3 mediates cellular responses to inhaled particular matter (e.g., PM10) and has recently been elegantly shown to have an important role in innate but not adaptive immune responses in airway epithelial cells [22]. A novel NLR termed NLRX-1 has been identified in nasal epithelium that is activated by double-stranded RNA and participates in rhinoviral-mediated disruption of polarized airway epithelial cell barrier function [23].…”
Section: Airway Epithelial Cells As the First Line Of Innate Immune Smentioning
confidence: 99%